A Review of the Removal of Dyestuffs from Effluents onto Biochar - Prakash Parthasarathy (10159511) (2022)
The study provides a review of various applications of biomass-derived biochars, waste-derived biochars, and modified biochars as adsorbent materials for removing dyestuff from process effluents. Processing significant amounts of dye effluent discharges into receiving waters can supply major benefits to countries which are affected by the water crisis and anticipated future stress in many areas in the world. When compared to most conventional adsorbents, biochars can provide an economically attractive solution. In comparison to many other textile effluent treatment processes, adsorption technology provides an economic, easily managed, and highly effective treatment option. Several tabulated data values are provided that summarize the main characteristics of various biochar adsorbents according to their ability to remove dyestuffs from wastewaters. Other Information Published in: Separations License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/separations9060139